PENTINGNYA INOVASI DALAM DUNIA PENDIDIKAN DI ERA DIGITAL - Karnita Sartina (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2023)
This study aims to analyze the role of digital technology innovation in enhancing educational quality and strengthening students' character. It also seeks to identify the challenges and opportunities in digital education transformation and evaluate the policies supporting the implementation of technology in education. The research method used is a literature review with a qualitative descriptive approach, where data is collected from various relevant sources, such as journals, academic books, and educational policy documents. Data analysis is performed using content analysis techniques to identify consistent thematic patterns. The results indicate that digital innovation plays a significant role in improving learning quality through online platforms, interactive applications, and blended learning, which also contributes to strengthening students' character. However, challenges such as the digital access gap and low digital literacy need to be addressed with progressive policies and continuous teacher training. The transformation of digital education should be implemented with an inclusive and sustainable approach